Diagnosis Sindrom Piriformis - Mahendrakrisna, Daniel (Cermin Dunia Kedokteran, 2019)
Sindrom piriformis adalah neuropati perifer kompresi muskulus piriformis pada nervus iskiadikus. Kelainan ini banyak ditemukan pada wanita dan cenderung luput dari diagnosis karena banyaknya penyakit dengan gejala sama. Aktivitas berlebihan dan duduk lama merupakan pencetus. Gejala dan pemeriksaan fisik sederhana seperti Pace sign, Freiberg sign, pyriformis sign, dan Beatty sign dapat membantu diagnosis. Tatalaksana mencakup farmakologi obat anti inflamasi non steroid, fisioterapi, psikoterapi, serta pembedahan.Piriformis syndrome (PS) is a neuropathy due to compression to sciatic nerve lying on piriformis muscle. PS are more commonly found in women. Excessive activities and sitting could be precipitating factors. PS is often misdiagnosed because of many diseases with similar symptoms. Physical signs, such as Pace sign, Freiberg sign, piriformis sign, and Beatty sign, could aid to diagnosis. Non-steroidal anti inflammatory agent, physioterapy, psychotherapy, and surgery could reduce the symptoms.Â